ChemInform Abstract: Three Cobalt(II)‐Linked P8W48 Network Assemblies: Syntheses, Structures, and Magnetic and Photocatalysis Properties. Issue 19 (13th May 2014) - Jiao, Yan‐Qing; Qin, Chao; Wang, Xin‐Long; Wang, Chun‐Gang; Sun, Chun‐Yi; Wang, Hai‐Ning; Shao, Kui‐Zhan; Su, Zhong‐Min
Abstract Compounds (IV) and (VII) crystallize in the triclinic space group P <![CDATA[1]]> <inline-graphic xlink:href="ark:/27927/pgg5f93vkg9" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> with Z = 1 (single crystal XRD).